Aplikasi Alarm Pergantian Jam Belajar Menggunakan Teknik Counter Berbasis Adruino - H Hafizah; A Amrullah; Z Panjaitan; R I GINTING (Jurnal MESIL (Mesin Elektro Sipil), 2021)
The automatic bell serves to signal the turn of the hour for each lesson, and there are no more picket officers who forget to ring the bell. This automatic bell will ring at the right time, so lesson changes are no longer a mess. Furthermore, the delay in changing study hours often results in the subsequent teaching and learning process being short of time in public elementary schools. As an example of the use of the Arduino Uno microcontroller which is used as an automatic school bell controller. One of the conveniences possessed by this automatic learning hour change alarm is a control system by inputting the school bell schedule into the Arduino Uno microcontroller, then the alarm for changing the learning hours for public elementary schools will activate automatically according to the adjusted school bell schedule input.